Hospital effect on infections after four major surgical procedures: outlier and volume–outcome analysis using all-inclusive state data. Issue 2 (October 2017) - Furuya-Kanamori, L.; Doi, S.A.R.; Smith, P.N.; Bagheri, N.; Clements, A.C.A.; Sedrakyan, A.
SUMMARY: Background: Hospital volume is known to have a direct impact on the outcomes of major surgical procedures. However, it is unclear if the evidence applies specifically to surgical site infections. Aims: To determine if there are procedure-specific hospital outliers [with higher surgical site infection rates (SSIRs)] for four major surgical procedures, and to examine if hospital volume is associated with SSIRs in the context of outlier performance in New South Wales (NSW), Australia. Methods: Adults who underwent one of four surgical procedures (colorectal, joint replacement, spinal and cardiac procedures) at a NSW healthcare facility between 2002 and 2013 were included. The hospital volume for each of the four surgical procedures was categorized into tertiles (low, medium and high). Multi-variable logistic regression models were built to estimate the expected SSIR for each procedure. The expected SSIRs were used to compute indirect standardized SSIRs which were then plotted in funnel plots to identify hospital outliers. Findings: One hospital was identified to be an overall outlier (higher SSIRs for three of the four procedures performed in its facilities), whereas two hospitals were outliers for one specific procedure throughout the entire study period. Low-volume facilities performed the best for colorectal surgery and worst for joint replacement and cardiac surgery. One high-volume facility was an outlier for spinal surgery. Conclusions: Surgical site infections seem to be mainly a procedure-specific, as opposed to a hospital-specific, phenomenon in NSW. The association between hospital volume and SSIRs differs for different surgical procedures.